Our impact - Schwab Foundation for Social Entrepreneurship (Schwab Foundation for Social Entrepreneurship)
The Schwab Foundation for Social Entrepreneurship launched its 2020 Impact Report which showcases the collective impact of the Schwab Foundation social entrepreneur community.
Keywords: Europe; Mesure d'impact; OBNL